Problems and trends of budget fund expenditures - N. N. Ablizina; S. V. Poltorykhina (Russian Journal of Economics and Law, 2014)
Objective: to define the directions of budget policy improvement in the sphere of the efficient use of financial resources with a view of the main strategic goal of the modern Russian state - the modernization of the Russian economy. Methods: abstract-logical method, horizontal and vertical comparative analysis. Results: The work presents the summarizing and critical evaluation of the modern budget policy of the Russian Federation in the sphere of budget means expenditures. Factors are analyzed which define the features of the modern budget policy in the studied sphere, as well as forms, techniques and tools of its implementation. The characteristic features and problems of its implementation are revealed. Scientific novelty: defining the interaction between the efficiency of budget means expenditure and the quality of economy modernization. The principles of the state budget policy are revealed in the sphere of means expenditure, its main elements and priority directions. The article also states that the inefficient expenditure of the budget means occurs first of all by the high level of corruption and shadow economy in the financial-budget sphere, especially in the regions. The shadow economy distorts the data about the national economy development, reduces taxation base and decelerates economic growths, which does not promote it modernization. The efficiency of means expenditure can also be ensured by state-private partnership. The state-private partnership development can become one more factor of the national economy modernization, especially under limited financial resources. Practical value: possibility to implement the proposed measures fro the budget policy modernization in the sphere of financial means expenditure for increasing the efficiency of their implementation.